Loss of innocence [compact disc, unabridged] - Patterson, Richard North (AudioGo, 2013)
June, 1968. America is in a state of turbulence, engulfed in civil unrest and uncertainty. Yet for Whitney Dane--spending the summer of her twenty-second year on Martha's Vineyard - life could not be safer, nor the future more certain. Educated at Wheaton, soon to be married, and the youngest daughter of the patrician Dane family, Whitney has everything she has ever wanted, and is everything her all-powerful and doting father, Charles Dane, wants her to be. But the Vineyard's still waters are disturbed by the appearance of Benjamin Blaine. An underprivileged, yet fiercely ambitious and charismatic young man, Blaine is a force of nature neither Whitney nor her family could have prepared for. As Ben's presence begins to awaken independence within Whitney, it also brings deep-rooted Dane tensions to a dangerous head. And soon Whitney's set-in-stone future becomes far from satisfactory, and her picture-perfect family far from pretty.